Engage for equity plus: Transforming academic health centers to sustain patient/community engaged research structures, policies, and practices - Shannon Sanchez-Youngman; Belkis Jacquez; Prajakta Adsul; Elizabeth Dickson; Tabia Henry Akintobi; LaShawn Hoffman; Lisa G. Rosas; Starla Gay; Jason A. Mendoza; Diane Mapes; John Oetzel; Donald Nease; et al. (Journal of Clinical and Translational Science)
Abstract